Merkel cell polyomavirus T-antigens regulate DICER1 mRNA stability and translation through HSC70 - Jiwei Gao (Elsevier, 2021)
Summary: Merkel cell carcinoma is an aggressive skin malignancy, mostly caused by Merkel cell polyomavirus (MCPyV). MCPyV T-antigens can induce mature microRNA expressions through the DnaJ domain, but its underlying mechanism is still unknown. Here, we report that the T-antigens induce protein expression and mRNA stability of DICER1, a key factor in microRNA biogenesis, through heat shock cognate 70 (HSC70). HSC70 directly interacts with the AU-rich elements (ARE) of DICER1 mRNA in both coding and 3′ untranslated region in the presence of MCPyV T-antigen. The T-antigen/HSC70 interaction could induce luciferase activity of synthetic ARE-containing reporter, as well as the stability of ARE-containing mRNAs, suggesting a broader role of MCPyV T-antigens in regulating multiple mRNAs via HSC70. These findings highlight a new role for the interaction of HSC70 and MCPyV T-antigens in mRNA regulation and an undescribed regulatory mechanism of DICER1 mRNA stability and translation through its direct interaction with HSC70.